A Continuous and Noninvasive Method to Estimate Pao2/Fio2 Ratio - Francis-Olivier Beauchamp, MD; Michaël Sauthier, MD, PhD (Critical Care Explorations, 2024)
OBJECTIVES:. To validate a method for continuously estimating the Pao2/Fio2 (PF) ratio in all critically ill pediatric patients using only standard continuous data monitoring. DESIGN:. Retrospective study on a high temporal resolution database. SETTING:. PICU in Montreal, QC, Canada. PATIENTS/SUBJECTS:. We included any patients admitted from May 2015 to May 2023 who had an arterial blood gas (ABG) with concurrent continuous pulsed oximetry saturation (Spo2) values. We used our previously validated mathematical model to determine the magnitude of hypoxemia by computing the estimated ePao2/Fio2 (ePF) ratio and comparing it to the Spo2/Fio2 (SF), using PF ratio as the reference standard. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. We analyzed a total of 20,828 ABGs. When Spo2 was below or equal to 97%, the ePF ratio showed a significantly better hypoxemia classification (none, light/moderate, or severe) than the SF ratio (0.80 vs. 0.72; p < 0.001), a lower fixed bias (16.26 vs. –35.24; p < 0.001), a lower mean absolute error (37.92 vs. 63.93; p < 0.001) and a lower proportional bias (slope of 1.01 vs. 0.81; p < 0.001). ePF ratio has also a better limits of agreement difference from Bland-Altman plot (248.10 vs. 292.45; p < 0.001) and coefficient of determination (0.68 vs. 0.59; p < 0.001). When Spo2 was above 97%, the ePF ratio had better classification with Kappa (0.53 vs. 0.43; p < 0.001) and lower fixed bias (–0.63 vs. 65.68; p < 0.001). CONCLUSIONS:. The PF ratio based on ePF allows for a continuous estimation of hypoxemia severity with a better performance than the SF ratio.